PHARMACOTHERAPY ALOPECIA ANDROGENETIC IN MEN - Januar Pramitha, Riezky; Sri Wiryawan, I.G.N; Linawati, Ni Made (E-Jurnal Medika Udayana; vol 2 no3 (2013):e-jurnal medika udayana)
Androgenetic alopecia is hair thinning due to the stimulation of hair follicles to androgens. Incidence in men is higher than in women, it is because men have a degree higher 5? reductase. This condition can cause both physical and psychological effects to the patient. Physical effects due to baldness cause hair loss as a function of protection against heat, cold and trauma. While psychologically can affect self-esteem and self-perception of the patient. Androgenetic alopecia in men influenced by the androgen dihydrotestosterone and genetic predisposition, although the physiology remains unclear. Modality in the management of androgenetic alopecia in males patients including pharmacotherapy, hair transplants and cosmetic approach. According to the Food and Drug Administration (FDA), there are two main drugs are safe and effective in the long term given to men with androgenetic alopecia are minoxidil and finasteride. Although the mechanism of action and route of administration are different, but both drugs have similar effectiveness in stopping the progression of androgenetic alopecia in men.
Keywords: androgenetic alopecia, minoxidil , finasteride